Health Canada and the Pharmaceutical Industry: A Preliminary Analysis of the Historical Relationship - Lexchin, Joel (Longwoods Publishing, 2013)
In the past two decades, Health Canada has been accused of favouring the pharmaceutical industry over the public in areas of pharmaceutical policy. This orientation has been tied to the introduction of user fees by the industry in 1994 that help finance key aspects of drug regulation. This paper provides a preliminary examination of the history of the relationship starting in 1939 until the mid-1980s in an attempt to discern whether 1994 really represented a key turning point. Clientele pluralism, a theory that explains the relationship between the state and interest groups, is used to explain the nature of the events described.